'Excess anxiety' and 'less anxiety': both depend on vestibular function. Issue 1 (February 2020) - Brandt, Thomas; Dieterich, Marianne
Abstract : Purpose of review: To present evidence of a functional interrelation between the vestibular and the anxiety systems based on a complex reciprocally organized network. The review focuses on the differential effects of various vestibular disorders, on psychiatric comorbidity, and on anxiety related to vertigo. Recent findings: Episodic vertigo syndromes such as vestibular migraine, vestibular paroxysmia, and Menière's disease are associated with a significant increase of psychiatric comorbidity, in particular anxiety/phobic disorders and depression. Chronic unilateral and bilateral vestibulopathy (BVP) do not exhibit a higher than normal psychiatric comorbidity. Anxiety related to the vertigo symptoms is also increased in episodic structural vestibular disorders but not in patients with chronic unilateral or bilateral loss of vestibular function. The lack of vertigo-related anxiety in BVP is a novel finding. Several studies have revealed special features related to anxiety in patients suffering from BVP: despite objectively impaired postural balance with frequent falls, they usually do not complain about fear of falling; they do not report an increased susceptibility to fear of heights; they do not have an increased psychiatric comorbidity; and they do not report increased anxiety related to the perceived vertigo. Subtle or moderate vestibular stimulation (by galvanic currents or use of a swing) may have beneficial effects on stress or mood state in healthy adults, and promote sleep in humans and rodents. The intimate structural and functional linkage of the vestibular and anxiety systems includes numerous nuclei, provincial and connector hubs, the thalamocortical network, and the cerebellum with many neural transmitter systems. Summary: The different involvement of emotional processes and anxiety – to the extent of 'excess anxiety' or 'less anxiety' – in structural vestibular disorders may be due to the specific dysfunction and whether the system activity is excited or diminished. Both psychiatric comorbidity and vertigo-related anxiety are maximal with excitation and minimal with loss of peripheral vestibular function.